(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Emerging viral diseases have become a significant concern for global public health, posing threats to human health, economies, and ecosystems. Emerging viral diseases (EVDs) have increasingly become a pressing concern for global public health, posing substantial threats not only to human health but also to economies and ecosystems. These diseases, often originating from zoonotic sources, rapidly spread through populations, leading to significant morbidity and mortality. The COVID-19 pandemic is a stark example, highlighting how quickly a novel virus disrupt health systems and economies worldwide. This paper explores the nature of emerging viral diseases, factors contributing to their emergence, and the challenges associated with their management and prevention. Through a review of current literature and case studies, the paper highlights the importance of surveillance, research, and international cooperation in addressing these threats. Key findings indicate that rapid urbanization, environmental changes, and increased human-animal interactions are critical factors in the emergence of new viral pathogens.